Promoting Pro-Poor Agricultural Growth in Rwanda : Challenges and Opportunities - World Bank (Washington, DC, 2014)
This report summarizes the findings of a study undertaken by the World Bank at the request of the Government of Rwanda. The study had three main objectives: (i) Validate the argument that agriculture has potential to become a leading engine of pro-poor growth in Rwanda and identify potential sources of rapid and sustainable growth within the agricultural sector; (ii) identify key actions that will be needed to unlock these sources of agricultural growth, and describe actions in other sectors that will be needed to support the successful implementation of the government's agricultural policy agenda; and (iii) confirm the congruence between the priority actions needed to stimulate increased agricultural growth and the policy reforms, institutional changes, and supporting investments envisioned under the Plan Strategique de Transformation Agricole (PSTA). This report consists of five sections, of which the introduction is the first. Section 2 describes the importance of agriculture in the economy of Rwanda and analyzes recent trends in the performance of the agricultural sector. Section 3 discusses possible future drivers of growth, considering both the demand and the supply side. Section 4 presents the results of a modeling exercise that explores the likely future impacts of alternative growth strategies on incomes, poverty, foreign exchange earnings, and food security. Section 5 concludes by discussing key actions within the agricultural sector that will be needed to stimulate sustainable pro-poor growth.